Adoption of Pigeon-Pea Production Technology in Udaipur District of Rajasthan (Indian Journal of Extension Education, 2010)
Pigeon Pea (Cajanus cajan L.) in gram all over the world mostly in tropical and sub-tropical countries. It is useful pulse crop in Asian countries too. The present study was conducted in Udaipur district of Rajasthan. A total of 160 pigeon-pea growns (including 80 tribals and 80 non-tribal farmers) were selected randomly. Results shown that majority of the farmers adopted upto medium level the production technology. It was also observed that difference in adoption of tribal and non-tribal farmers was significant.